Surface-Based Morphometry of Cortical Thickness and Surface Area Associated with Heschl's Gyri Duplications in 430 Healthy Volunteers - Marie, Damien; Maingault, Sophie; Crivello, Fabrice; Mazoyer, Bernard; Tzourio-Mazoyer, Nathalie (Frontiers in Human Neuroscience, 2016)
We applied Surface-Based Morphometry to assess the variations in cortical thickness (CT) and cortical surface area (CSA) in relation to the occurrence of Heschl’s gyrus (HG) duplications in each hemisphere. Four hundred thirty healthy brains that had previously been classified as having a single HG, Common Stem Duplication (CSD) or Complete Posterior Duplication (CPD) in each hemisphere were analyzed. To optimally align the HG area across the different groups of gyrification, we computed a specific surface-based template composed of 40 individuals with a symmetrical HG gyrification pattern (20 single HG, 10 CPD, 10 CSD). After normalizing the 430 participants’ T1 images on this specific template, we separately compared the groups composed of participants with a single HG, CPD and CSD in each hemisphere. The occurrence of a duplication in either hemisphere was associated with an increase in CT posterior to the primary auditory cortex that may be the neural support of expertise and better abilities in either the speech or music processing domains, which are associated with the duplication. A decrease in CSA in the planum temporale was detected in cases with a duplication in the left hemisphere. In the right hemisphere, a medial decrease in CSA and a lateral increase in CSA were present in HG when a CPD occurred together with an increase in CSA in the depth of the superior temporal sulcus (STS) in CSD compared to a single HG. These variations associated with duplication might be related to the functions that they process jointly within each hemisphere: temporal processing and speech in the left and spectral processing and music in the right.